Is There a Relationship Between Gestational Diabetes and Perinatal Depression?. Issue 4 (July 2018) - Clevesy, Marcia A.; Gatlin, Tricia K.; Strebel, Kord T.
Abstract : Abstract: Perinatal depression (PND) is one of the leading complications associated with childbirth. Early detection and treatment of depression, particularly during the perinatal period, is essential for the promotion of positive maternal–child outcomes. Gestational diabetes mellitus (GDM) has been suggested as a confounding factor associated with PND. Concerns associated with PND include interference with maternal–newborn bonding and long-term effects of neurobehavioral consequences. An exemplar case describing one woman's experience with GDM and her subsequent complications associated with PND is presented to discuss maternal depression and its plausible association with GDM. Recommendations include universal screening with the validated Edinburgh Postnatal Depression Scale screening tool during the early perinatal period to reduce incidence of maternal–newborn complications associated with PND and promote underpinnings for best practice. Abstract : The association between gestational diabetes and perinatal depression may be supported by shared physiologic and psychosocial influences, which appear to be bidirectional among these co-morbid conditions. The combination of gestational diabetes and perinatal depression requires further assessment and intervention as there are increased risks for adverse outcomes for mothers with these conditions and their babies.